The Term "Self-Directed Learning"-Back to Knowles, or Another Way to Forge Ahead? - Van der Walt, Johannes L. (Journal of research on christian education, 2019)
The term self-directed learning has since its seminal definition in 1975 by Malcolm S. Knowles acquired a range of meanings, which has led to communication difficulties about this subject. Examination of self-directed learning from a biblical ontological-anthropological perspective reveals that, although the notion of self-directed learning as a mechanistic or deterministic process should be questioned, Knowles and colleagues were correct in ameliorating the "process part" of the definition of self-directed learning by emphasizing the freedom and agency of the learner as steward of creation. Researchers wishing to deviate from the approach by Knowles and colleagues are compelled to explain what the term designates in their particular project.